Student perceptions of a new integrated course in clinical methods for medical undergraduates - HASTINGS, A. M; FRASER, R. C; MCKINLEY, R. K (Medical education, 2000)
Context In line with recent General Medical Council recommendations a new, 8‐week integrated course in clinical methods has been introduced into the undergraduate curriculum at Leicester University. Objectives To describe student perceptions of the course and to identify areas for improvement. Design A questionnaire survey. Settings These were 50 general practices, three teaching hospitals and the academic Department of General Practice and Primary Health Care. Subjects A total of 180 third‐ and fourth‐year medical students. Results The questionnaires were completed by 93% of students. The latter expressed higher satisfaction with practice teaching compared with hospital teaching, on a 5‐point scale, with regard to questions on ‘teaching content’ (4·0 vs. 2·7, P < 0·0001) and ‘teaching process’ (4·1 vs. 2·7 P < 0·0001), which was reinforced by free text comments. Of the respondents, 92% agreed that their teaching practice had satisfied the required teaching timetable and 87% of students found their departmental tutor enthusiastic and stimulating. Conclusion It is possible to deliver an integrated course in clinical methods, teaching generic clinical skills, in a mix of hospital and practice settings. Nevertheless there were substantial differences in student perceptions of the relative quality and impact of teaching in the two settings. This may be related to the more detailed programme of preparation of practice teachers and the greater extent to which practice teachers were required, and able, to create protected time for the teaching task. These differences should be minimized if hospital teachers undergo similar preparation for the teaching task and have similar levels of protected teaching time.